The effectiveness of cyclooxygenase-2 inhibitors and evaluation of angiogenesis in the model of experimental colorectal cancer - Gungor, Hilal; Ilhan, Nevin; Eroksuz, Hatice (Elsevier France-Editions Scientifiques Medicales Elsevier, 2018)
Colorectal cancer (CRC) is an important cause of cancer-related deaths worldwide. Early diagnosis and treatment of CRCs are of importance for improving the survival. In the present study, we studied the effects of nonsteroidal anti-inflammatory drugs (NSAIDs)-induced chemopreventive effects on tumor development incidence and angiogenesis in experimental CRC rats. 1,2-Dimethylhydrazine dihydrochloride (DMH) was used as cancer-inducing agent and two NSAIDs (celecoxib and diclofenac) were given orally as chemopreventive agents. Histopathological and immuno histochemical evaluations were performed in colorectal tissue samples, whereas angiogenesis parameters were studied in blood samples. Histopathological examination showed that adenocarcinoma (62.5%), dysplastic changes (31.25%) and inflammattory changes (6.25%) were detected in DMH group, whereas no pathological change was observed in control rats. In treatment groups, there was marked decrease in adenocarcinoma rate (30% and 10%, respectively). A significant increase was detected in MMP-2, MMP-9 levels and MMP-2/ TIMP-2 ratio in DMH group as compared with controls and treatment groups. In immunohistochemical evaluations, there was an increase in intensity and extent of staining of MMP-2 and MMP9 in DMH group as compared to controls and treatment groups. The decrease in celecoxib group was more prominent. Overall, it was concluded that NSAIDs, particularly cyclooxygenase-2 (COX-2) inhibitors, might have a protective effect on CRC development and slow down progression of tumor in a DMH-induced experimental cancer model. One of the possible mechanisms in the chemoprevention of colon cancer seems to be inhibition of angiogenesis by diclofenac and celecoxib.
Keywords: Angiogenesis; Colorectal cancer; COX-2 inhibitors; NSAI drugs